Accelerated Intermittent Theta Burst Stimulation for Suicide Risk in Therapy-Resistant Depressed Patients: A Randomized, Sham-Controlled Trial - Desmyter, Stefanie; Duprat, Romain; Baeken, Chris; Van Autreve, Sara; Audenaert, Kurt; van Heeringen, Kees (Frontiers in Human Neuroscience, 2016)
Objectives We aimed to examine the effects and safety of accelerated intermittent Theta Burst Stimulation (iTBS) on suicide risk in a group of treatment-resistant unipolar depressed patients, using an extensive suicide assessment scale. Methods In 50 therapy-resistant, antidepressant-free depressed patients, an intensive protocol of accelerated iTBS was applied over the left dorsolateral prefrontal cortex in a randomized, sham-controlled cross-over design. Patients received 20 iTBS sessions over 4 days. Suicide risk was assessed using the Beck Scale of Suicide ideation (BSI). Results The iTBS protocol was safe and well-tolerated. We observed a significant decrease of the BSI score over time, unrelated to active or sham stimulation and unrelated to depression-response. No worsening of suicidal ideation was observed. The effects of accelerated iTBS on mood and depression severity are reported in Duprat et al. (2016). The decrease in suicide risk lasted up to one month after baseline, even in depression non-responders. Conclusions This accelerated iTBS protocol was safe. The observed significant decrease in suicide risk was unrelated to active or sham stimulation and unrelated to depression response. Further sham-controlled research in suicidal depressed patients is necessary. (clinicaltrials.gov identifier: NCT01832805)